Pediatric oral health: community-based participatory research - Marcella Ogenchuk; Juanita Graham; Gerry Uswak; Holly Graham; Robert Weiler; Vivian R. Ramsden (BMC, 2022)
Abstract Background The most common chronic disease affecting children in Canada is dental caries. The objective of this study was to explore, identify, and address the strengths and barriers related to oral health services with an independent Indigenous community in Saskatchewan. Methods Community-based participatory research used interviews with Elders, health care providers, teachers, and parents/guardians of elementary school-aged children. The research focused on the development of genuine partnerships with the community. During data collection, the findings/results were returned to the community to establish direction, build success, and establish next steps. Thematic analysis was undertaken with the community. Descriptive statistics were analyzed using SPSS. Results The most commonly identified themes included: community resilience; the need for resource development and process to improve oral health literacy and skills; and how access to care barriers dually affected and related to personal and community cost, time, and human resources. Conclusions The research process involved the co-creation of tools to identify strengths within the community and drive opportunities for change; subsequently generating solutions to the practical problems and potentially transform the health system accessed by the community.